Use of GnRH Analogues in the Reduction of Submucous Fibroid for Surgical Hysteroscopy: A Systematic Review and Meta-Analysis - Corrêa,Thayane Delazari (2020)
Abstract Objective Gonadotropin-releasing hormone analogues (GnRH-a) have been used preoperatively before hysteroscopic myomectomy to decrease the size and vascularization of the myomas, but evidence to support this practice is weak. Our objective was to analyze the use of GnRH-a in the reduction of submucous fibroid as a facilitator for surgical hysteroscopy from published clinical trials. Data sources Studies from electronic databases (Pubmed, Scielo, EMBASE, Scopus, PROSPERO), published between 1980 and December 2018. The keywords used were fibroid, GnRH analogue, submucous, histeroscopy, histeroscopic resection and their correspondents in Portuguese. Study selection The inclusion criteria were controlled trials that evaluated the GnRH-a treatment before hysteroscopic resection of submucous myomas. Four clinical trials were included in the meta-analysis. Data collection Two review authors extracted the data without modification of the original data, using the agreed form. We resolved discrepancies through discussion or, if required, we consulted a third person. Data synthesis The present meta-analysis included a total of 213 women and showed no statistically significant differences in the use of GnRH-a compared with the control group for complete resection of submucous myoma (relative risk [RR]: 0.94; 95%; confidence interval [CI]: 0.80-1.11); operative time (mean difference [MD]: - 3.81; 95%;CI : - 3.81-2.13); fluid absorption (MD: - 65.90; 95%;CI: - 9.75-2.13); or complications (RR 0.92; 95%;CI: 0.18-4.82). Conclusion The present review did not support the routine preoperative use of GnRH-a prior to hysteroscopic myomectomy. However, it is not possible to determine its inferiority when compared with the other methods due to the heterogeneity of existing studies and the small sample size.